MENJUNJUNG ASAS KEADILAN BERUMAH TANGGA ANTARA KEDUA PIHAK KELUARGA DENGAN PELAKSANAAN SISTEM PERKAWINAN PADA GELAHANG DI BALI - Budiasih, Ni Made (VYAVAHARA DUTA, 2018)
Balinese perception of marriage in gelahang including positive, because it is seen as a reality that already exist in society, and never questioned. The inheritance system in the family that carries out the marriage in gelahang in Bali basically adheres to the parental principle, namely the inheritance system that inherits the family of the male and female families. The pattern of parenting in the family formed through marriage in gelahang generally chooses the pattern of democratic care that is characterized by the rights and obligations of parents and children is the same, in the sense that they are complementary. The process of execution of marriage in gelahang is not different from ordinary marriage process, and generally executed by the process of marriage, which was preceded by dating period. In the marriage at gelahang there are two relatively similar ceremonies, namely at the residence of the bridegroom and at the residence of the bride?s. The equation of marriage in gelahang with marriage nyentana namely: equally an alternative marriage, based on love the same love, there are religious witnesses (banten ceremony) and social witness (community) and both want to get offspring. While the difference is that marriage in gelahang status of men and women there is no change in status, so often called parental. The positions of born children are held jointly, unless there is another agreement. An important aspect of marriage in gembles that is rarely encountered is an agreement between husband and wife witnessed by the families of both parties, the agreement can be written and can be verbal.